Urgent Creation of a Palliative Care Team in a Small Hospital During the COVID Crisis. (March 2021) - Martinez, Nydia; Tanev, Hilah; Gurevich, Samuel; Davis, Candilla; Cazeau, Mirlande; Mehta, Jinesh; Gillenwater, Samantha; Daya, Andrew; Rahaghi, Franck
The COVID-19 pandemic created a global health emergency that has changed the practice of medicine and has shown the need for palliative care as an essential element of hospital care. In our small South Florida hospital, a palliative care service was created to support the frontline caregivers. Thanks to the hospital support, our team was formed rapidly. It consisted of 3 advanced care practitioners, a pulmonary physician with palliative care experience and the cooperation of community resources such as hospice and religious support. We were able to support patients and their families facilitating communication as visitation was not allowed. We also addressed goals of care, providing comfort care transition when appropriate, and facilitating allocation of scarce resources to patients who were most likely to benefit from them. With this article we describe a simplified framework to replicate the creation of a Palliative Care Team for other hospitals that are experiencing this need.